TikTok as a creative media by content creators in promoting products - Winda Putriani; Anis Endang Endang; Sri Narti (Jurnal STIA Bengkulu, 2023)
TikTok is a media to promote product at social media by using creative and interesting content. This research purpose is to find out TikTok as creative media by content creator in promoting product, this research is qualitative research. The theory which used in this research is about marketing mix according to Rangkuti (2009) which involves advertising, sales promotion, personal selling and direct marketing. The result of this research shows that TikTok as creative media by content creator. From TikTok account @enny_230221 who has succeeded in promoting corn ice product by using five marketing mix, the selling is by using content video. The user also active in responding the comment positively. The personal selling is conducted directly while selling the corn ice at the location. While the direct marketing, the user uses comment and direct message feature to communicate directly with audience. Marketing mix has been done by Eni Lestari totally and succeed. It can be seen from the positive comment from customer can give positive influence such as increase the selling every day. The TikTok account @enny_230221 has implement marketing mix strategy very well.